Triglyceride Can Predict the Discordance between QCT and DXA Screening for BMD in Old Female Patients - Xu, Dongjiang; di Wang, Ke; Yang, Jianhong (Disease Markers, 2020)
Summary. Bone mineral density (BMD) data and biochemical indexes of the elderly women in the cadre department were analyzed retrospectively to find out the relationship between the biochemical indexes and the different screening results between dual-energy X-ray absorptiometry (DXA) and quantitative computed tomography (QCT). Purpose. This study is aimed at exploring which indicator can predict the discordance between DXA and QCT. Methods. 192 female patients who took BMD screening tests by QCT and DXA were recruited, and the biomarkers were analyzed to study the relationship between the biomarkers and the discordance of two BMD screening methods. Results. There are 42, 78, and 72 female patients in the normal, osteopenia, and osteoporosis groups defined by DXA and 6, 54, and 132 female patients in the corresponding group defined by QCT. DXA was less sensitive than QCT. Cholesterol (CHO) and triglyceride (TG) were all negatively correlated with the discordance between these two methods. When TG>0.89 mmol/L, the QCT result would be the same as the DXA’s; otherwise, there should be discordance between QCT and DXA. Conclusions. Triglyceride can be used to predict the discordance between QCT and DXA, and clinicians can evaluate patients’ DXA results based on patient triglyceride or cholesterol results as a supplement to QCT results.